Implementation CorelDraw as the Idea of Entrepreneurial Student Boarding School Al–Iqbal Surabaya with Lean Startup Approach - Ronggo Alit; Chrystia Aji Putra (Future Science)
As one of the educational institutions, pesantren is required to accelerate and transform significantly. If the first scope of output is limited to the religious dimension alone, then nowadays pesantren graduates are expected to contribute in many aspects of community life. This is the opportunity and challenge of boarding school in developing science and technology education. In an effort to fulfill these demands, pesantren established formal education which besides teaching religious knowledge, also taught general science. Therefore, the mastery of science and technology is a must for us, one of them is in the field of information technology. The development of applications in the field of information technology has a major impact in various areas of life, not least in the field of creative industries such as printing, digital image processing, and graphic design. This requires us to provide training to students or students so that they can keep up with them and be able to use them for their supplies after they graduate. Some image processing applications have been developed. However, the popular and widely used app for the task is CorelDraw. CorelDraw is a computer application for processing on line 2 vectors. This application also often has an important role in the work field of publications or printing, as well as other areas that need the process of visualization. At Al-Iqbal Pesantren this example of a place that has not utilized a design technology to support internal and external activities such as making brochures, articles and so forth. With an application from CorelDraw, Al-Iqbal Pesantren will be able and able to make various products based on design technology to support existing activities in Pesantren AL-Iqbal and also can create entrepreneurship for students also become more valuable for the pesantren itself and able to create the ability on the use of design technology.